Estudos sobre bilinguismo: uma revisão bibliográfica sistematizada - Watthier, Marina Koltz (2022)
Current knowledge about bilingualism comes from different fields of knowledge. As it is a relatively new research topic, there are different approaches to understanding the bilingual individual and their particularities. The present work seeks to provide an overview of the subject in contemporary times and gather, through a systematic bibliographic review, recent research (2018-2022) on bilingualism and the contributions of diverse areas of knowledge to the study of the topic. From the search term "bilingual children language development" on the Capes Journal Portal, refinements were made so that presented analysis focus on 30 publications, all in English. Therefore, the research synthesizes these studies in a discussion that allows to identify the main research trends that improve current knowledge in the field of education and formation of bilingual contexts. The analyzes highlight psycholinguistics, psychology, education, phonoaudiology and neurology as main areas of knowledge that publish on the subject and the recurrent themes identified in these research are language disorders, autism spectrum disorder and the influence that cultural and demographic aspects exert on bilingualism, concluding that bilingualism is a comprehensive research area that brings contributions from different fields of knowledge with different perspectives and directions.